KEEFEKTIFAN SISTEM POIN DALAM PENINGKATAN KEDISIPLINAN PESERTA DIDIK DI UPT SMAN 5 TANA TORAJA - Chrisma Yanti; Andi Aco Agus; Muh. Sudirman (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2022)
Abstract : Research Objectives: (1) to find out the implementation of the points system in improving the discipline of students at UPT SMAN 5 Tana Toraja, (2) to find out the supporting and inhibiting factors implementation of the points system in improving the discipline of students. Data collection techniques through observation, interviews, and documentation. Data obtained from interviews with 25 students with purposive sampling technique, representatives of Science, Social, Pancasila and Civic teacher, teachers in the field of student affairs, and the principal of UPT SMAN 5 Tana Toraja, with supporting data such as student violation archives, and point system guidelines of UPT SMAN 5 Tana Toraja. The validity of the data is checked using the data source triangulation technique. The data from the research was processed using a type of research called descriptive technique. The results show that: (1) the implementation of the point system at UPT SMAN 5 Tana Toraja in improving the discipline of students has been quite effective, this know from the results of research with several informants in the implementation process consisting of several stages, namely starting from the process of forming a point system socialization committee preparing point system guidelines and point system socialization. Students will be given a limit of 100 points, the given guidance to students who commit violations carried out three times involving the parent, homeroomteacher, BK, vice head of student affairs and the principal with the criteria, 30 point for the first call, 50 points for the second call, 75 points for summons third with the coaching process provided can make students more aware of the rules that apply in school (2) Supporting factors for the implementation of this point system are students who have self-awareness and motivation, the presence of support and motivation from parents, and the absence of discrimination in sanctioning violating learners. The inhibiting factor for the implementation of the point system is the factor of oneself, where the disposition of the learners is difficult to manage, factor of teachers who have an indifferent attitude towards learners who violate the rules, vehicle factor where the lack of public transportation causes a large number of students who often commit violations, in this case they came late to school. Abstrak: Penelitian ini bertujuan untuk: (1) mengetahui pelaksanaan sistem poin dalam peningkatan kedisiplin peserta didik di UPT SMAN 5 Tana Toraja, (2) mengetahui faktor pendukung dan penghambat pelaksanaan sistem poin dalam peningkatan kedisiplin peserta didik. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Data yang diperoleh dari hasil wawancara dengan 25 orang peserta didik dengan teknik purposive sampling, perwakilan guru IPA, IPS, PPKn dan guru Bidang Kesiswaan serta Kepala Sekolah UPT SMAN 5 Tana Toraja dengan data penunjang seperti asrip pelanggaran peserta didik dan pedoman sistem poin UPT SMAN 5 Tana Toraja. Pengecekan keabsahan data dengan teknik triangulasi sumber data. Data yang telah diperoleh dari hasil penelitian diolah dengan jenis penelitian deskriftif. Hasil penelitian menunjukkan bawah: 1) pelaksanaan sistem poin di UPT SMAN 5 Tana Toraja dalam meningkatkan kedisiplinan peserta didik sudah cukup efektif, hal ini diketahui dari hasil penelitian dengan beberapa informan yang dalam proses pelaksanaannya terdiri dari beberapa tahapan yaitu mulai dari proses pembentukan panitia sosialisasi sistem poin, penyusunan pedoman sistem poin dan sosialisasi sistem poin. Peserta didik akan diberi batasan 100 poin, kemudian diberikan pembinaan kepada peserta didik yang melakukan pelanggaran sebanyak tiga kali yang melibatkan orang tua, wali kelas, BK, wakasek bidang kesiswaan dan kepala sekolah dengan kriteria, 30 poin panggilan pertama, 50 poin panggilan kedua, 75 poin panggilan ketiga, dengan proses pembinaan membuat peserta didik lebih sadar akan aturan yang berlaku di sekolah 2) faktor pendukung pelaksanaan sistem poin ini yaitu peserta didik yang memiliki kesadaran diri dan motivasi, adanya dukungan dan motivasi dari orang tua, menghindari diskriminasi dalam pemberian sanksi kepada peserta didik yang melanggar. Faktor penghambat pelaksanaan sistem poin yaitu watak peserta didik yang sulit untuk diatur, guru yang memiliki sikap tidak pedulih terhadap peserta didik yang melanggar peraturan, faktor kendaraan dimana kurangnya angkutan umum yang menyebabkan banyaknya peserta didik yang sering melakukan pelanggaran dalam hal terlambat datang ke sekolah. Kata Kunci : Sistem Poin dan Kedisiplinan